Chicken anemia virus causes apoptosis of thymocytes after in vivo infection and of cell lines after in vitro infection. - Jeurissen, S H (1992)
After infection of 1-day-old chickens, chicken anemia virus (CAV) causes a complete depletion of the thymic cortex by day 14. Since cell death can be caused either by necrosis or by apoptosis, we investigated which type of cell death occurs after in vivo and in vitro infections with CAV. Using electron microscopy and biochemical methods, we demonstrated that CAV induces apoptosis of cortical thymocytes after in vivo infection and of lymphoblastoid cell lines after in vitro infection. At day 13 after in vivo infection, virus-like particles were detected in apoptotic bodies that were absorbed by epithelial cells. These results show that apoptosis, a phenomenon that has been observed for a few other viruses, is also an important phenomenon during the pathogenesis of CAV.